Amyloid-beta clearance in Alzheimer's disease - Robert Marr; Eliezer Masliah (Frontiers Media SA, 2021)
Strong evidence continues to accumulate indicating that amyloid-beta (Aß) is a central part of Alzheimer’s disease (AD) pathogenesis in spite of the negative evidence coming from failed clinical trials. Therefore, mechanisms of clearance of Aß are of great interest in understanding AD pathogenesis and the development of effective treatments. This topic focuses on the issues related to Aß clearance in AD. The topics covered include proteases that degrade Aß and their localization, regulation, and functions. This topic also covers issues related to clearance through uptake by glia and through low-density lipoprotein (LDL) receptor mediated mechanisms. Signal transduction related to AD pathology and clearance is also addressed. Finally, immunotherapy and other novel therapeutic approaches are discussed.